2021
DOI: 10.1097/jom.0000000000002389
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination and Asymptomatic Infection

Abstract: Objective: To determine the incidence of COVID-19 and the duration of sick leave among asymptomatic healthcare workers (HCWs) after vaccination with BNT162b2. Methods: From October 2020 to March 2021, we determined the incidence of COVID-19 in a cohort of 671 asymptomatic HCWs before and after the vaccination. We also analyzed the days required to obtain a negative RT-PCR result after infection. Results: Prior to vaccination 105 (15.6%) HCWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The authors reported a rate of 1.6% after the first vaccine dose and 6.1% after the second [ 36 ]. Sick leave following vaccination is certainly an important aspect to consider, but it should be regarded in light of the fact that vaccination reduces HW sick leave due to infection and that it most likely reduces the duration of sick leave when infection occurs despite vaccination [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a rate of 1.6% after the first vaccine dose and 6.1% after the second [ 36 ]. Sick leave following vaccination is certainly an important aspect to consider, but it should be regarded in light of the fact that vaccination reduces HW sick leave due to infection and that it most likely reduces the duration of sick leave when infection occurs despite vaccination [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sick leave period was longer, with a duration of about 35 days, but the study is not comparable to ours due to main differences in study population (general population, not only HCWs) and because those who contracted the infection received sickness benefit during the period from 1 March to 31 August 2020 [ 26 ]. A further study, in Northern Italy, focused on HCWs; in addition to a decrease in incidence following vaccination, the median sick leave period was 12 days for unvaccinated HCWs and 11 days for vaccinated HCWs [ 18 ]. Our study mainly focused on the evaluation of variations of sick leave period with chronological time; therefore, it was in correlation with vaccination times, COVID-19 variants, and changes in the bureaucratic management of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the pandemic has led to an increase in sick leave periods among the HCWs [ 15 , 16 ], that vaccinated HCWs have a reduced incidence and a shortened sick leave length than before vaccination [ 18 ], that return-to-work time for fully vaccinated HCWs was significantly shorter than that of partially vaccinated/unvaccinated HCWs, that fully vaccinated HCWs also showed milder symptom profiles compared to partially vaccinated and unvaccinated HCWs [ 19 ], and that sick leave utilization among HCWs declined significantly after vaccines became available [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 3,4 found that sick leave utilization among healthcare workers (HCW) declined significantly after vaccines became available. However, studies have not compared the sick leave utilization of vaccinated vs. unvaccinated employees.…”
Section: Introductionmentioning
confidence: 99%